A Bibliometric Analysis of the Implementation of Big Data in the Managerial Decision-Making Process - Utomo, Ekwan Setyo; Siti Mujanah; Yanto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
Some scientific publications related to big data have been carried out; viral marketing that occurs on social media can be one way to market a product or service, and this article aims to provide information regarding research trends that have been published on the topic of viral marketing in the 2000-2024 periods. The method used in this study was to identify the number of journals using Harzing's Publish or Perish software as well as a bibliometric analysis using VOSviewer. The results showed that there were 987 publications with 21457 citations and 2145.7 cites/year that discussed viral marketing. There are five main clusters based on the results of the bibliometric analysis. This article also provides information related to research topics that have not been widely carried out, so that it can provide benefits for stakeholders who  may need it for further research